The Development of the DDads Questionnaire: Awareness, Knowledge and Attitudes of the General Population Towards Paternal Depression - Vermeulen, Joeri; Buyl, Ronald; D'haenens, Florence; Demedts, Dennis; Tricas-Sauras, Sandra; Haddani, Ihsane; Fobelets, Maaike (Frontiers in Psychiatry, 2021)
Objectives: Paternal perinatal depression affects approximately 10% of new fathers and is known to have a negative impact on men’s relationship with their partner as well as with their baby. The attitudes of the general population towards paternal depression have received scant attention in literature. A better understanding of paternal depression might improve the health literacy of the population and assist professionals and policy makers to adequately address this issue, to ultimately refine existing health care alternatives for them. This paper describes the Belgian development, face and content validation of the DDads (Depression in Dads) questionnaire. Its focus is to identify the awareness, knowledge and attitudes of the general population towards paternal perinatal depression. Study design: The DDads was developed using a three-step model with the following phases: (1) identification of the content domain, (2) item generation and (3) construction of the questionnaire. For the DDads validation a (a) Delphi method with content experts (n=17) and (b) a cognitive debriefing method with lay experts (n=20) were used to assess the clarity, relevance, wording and layout. Results: The questionnaire consists of three main components comprising: (1) three questions on awareness, (2) three questions on knowledge and (3) one question on attitudes and beliefs. After round one validation, all questions were considered content valid for relevance (I-CVI 0.94-1.00), and six questions for clarity (I-CVI 0.65-1.00). Scale content (S-CVI/Ave 0.93) and face validity (Face Validity Index 1.00) was obtained. One question was revised and split into two questions in a second round. For one of these questions, item content (0.80-0.93), scale content (0.92) and face validity (1.00) was reached. The one question, exploring the causes of paternal perinatal depression, remained inappropriate and was removed from the DDads. One last question was removed after interviews with lay experts. Conclusions: We developed an instrument to establish awareness, knowledge and attitudes of the general population towards paternal perinatal depression in Belgium. The DDads can be valuable in identifying knowledge gaps. It can help to inform policy makers and health professionals to identify gaps and predisposed attitudes in society towards paternal depression which may hinder appropriate management.